Fluid and White Matter Suppression: New Sensitive 3 T Magnetic Resonance Imaging Contrasts for Cortical Lesion Detection in Multiple Sclerosis. Issue 9 (3rd September 2022) - Müller, Jannis; La Rosa, Francesco; Beaumont, Jeremy; Tsagkas, Charidimos; Rahmanzadeh, Reza; Weigel, Matthias; Bach Cuadra, Meritxell; Gambarota, Giulio; Granziera, Cristina
Abstract : Objective: Cortical lesions are common in multiple sclerosis (MS), but their visualization is challenging on conventional magnetic resonance imaging. The uniform image derived from magnetization prepared 2 rapid acquisition gradient echoes (MP2RAGEuni ) detects cortical lesions with a similar rate as the criterion standard sequence, double inversion recovery. Fluid and white matter suppression (FLAWS) provides multiple reconstructed contrasts acquired during a single acquisition. These contrasts include FLAWS minimum image (FLAWSmin ), which provides an exquisite sensitivity to the gray matter signal and therefore may facilitate cortical lesion identification, as well as high contrast FLAWS (FLAWShco ), which gives a contrast that is similar to one of MP2RAGEuni . In this study, we compared the manual detection rate of cortical lesions on MP2RAGEuni, FLAWSmin, and FLAWShco in MS patients. Furthermore, we assessed whether the combined detection rate on FLAWSmin and FLAWShco was superior to MP2RAGEuni for cortical lesions identification. Last, we compared quantitative T1 maps (qT1) provided by both MP2RAGE and FLAWS in MS lesions. Materials and Methods: We included 30 relapsing-remitting MS patients who underwent MP2RAGE and FLAWS magnetic resonance imaging with isotropic spatial resolution of 1 mm at 3 T. Cortical lesions were manually segmented by consensus of 3 trained raters and classified as intracortical or leukocortical lesions on (1) MP2RAGE uniform/flat images, (2) FLAWSmin, and (3) FLAWShco . In addition, segmented lesions on FLAWSmin and FLAWShco were merged to produce a union lesion map (FLAWSmin + hco ). Number and volume of all cortical, intracortical, and leukocortical lesions were compared among MP2RAGEuni, FLAWSmin, and FLAWShco using Friedman test and between MP2RAGEuni and FLAWSmin + hco using Wilcoxon signed rank test. The FLAWS T1 maps were then compared with the reference MP2RAGE T1 maps using relative differences in percentage. In an exploratory analysis, individual cortical lesion counts of the 3 raters were compared, and interrater variability was quantified using Fleiss ϰ. Results: In total, 633 segmentations were made on the 3 contrasts, corresponding to 355 cortical lesions. The median number and volume of single cortical, intracortical, and leukocortical lesions were comparable among MP2RAGEuni, FLAWSmin, and FLAWShco . In patients with cortical lesions (22/30), median cumulative lesion volume was larger on FLAWSmin (587 μL; IQR, 1405 μL) than on MP2RAGEuni (490 μL; IQR, 990 μL; P = 0.04), whereas there was no difference between FLAWSmin and FLAWShco, or FLAWShco and MP2RAGEuni . FLAWSmin + hco showed significantly greater numbers of cortical (median, 4.5; IQR, 15) and leukocortical (median, 3.5; IQR, 12) lesions than MP2RAGEuni (median, 3; IQR, 10; median, 2.5; IQR, 7; both P < 0.001). Interrater agreement was moderate on MP2RAGEuni (ϰ = 0.582) and FLAWShco (ϰ = 0.584), but substantial on FLAWSmin (ϰ = 0.614). qT1 in lesions was similar between MP2RAGE and FLAWS. Conclusions: Cortical lesions identification in FLAWSmin and FLAWShco was comparable to MP2RAGEuni . The combination of FLAWSmin and FLAWShco allowed to identify a higher number of cortical lesions than MP2RAGEuni, whereas qT1 maps did not differ between the 2 acquisition schemes.